2014
DOI: 10.1063/1.4903003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of global-scale turbulence in a librating ellipsoid

Abstract: We present laboratory experimental results demonstrating that librational forcing of an ellipsoidal container of water can produce intense motions through the mechanism of a libration driven elliptical instability (LDEI). These libration studies are conducted using an ellipsoidal acrylic container filled with water. A particle image velocimetry method is used to measure the 2D velocity field in the equatorial plane over hundreds libration cycles for a fixed Ekman number, E = 2 × 10 −5 . In doing so, we recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
69
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(80 citation statements)
references
References 63 publications
(91 reference statements)
11
69
0
Order By: Relevance
“…As shown here, the fundamental quantity to be considered is, therefore, the ratio between geostrophic flows and 3D modes, which depends on the specifics of the considered system and has been mostly neglected when comparing different rotating turbulence configurations. In previous experiments and simulations in spherical or ellipsoidal geometries, the geostrophic modes resulting from the nonlinear interactions of inertial waves manifest themselves as zonal flows, i.e., mean steady axisymmetric flows pervading the fluid interior [16,17,[51][52][53] (see [54], however). Their amplitudes tend to be proportional to β 2 E −α , with α ranging from 0 to 2 [52,55,56], depending on the excitation frequency.…”
Section: -2mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown here, the fundamental quantity to be considered is, therefore, the ratio between geostrophic flows and 3D modes, which depends on the specifics of the considered system and has been mostly neglected when comparing different rotating turbulence configurations. In previous experiments and simulations in spherical or ellipsoidal geometries, the geostrophic modes resulting from the nonlinear interactions of inertial waves manifest themselves as zonal flows, i.e., mean steady axisymmetric flows pervading the fluid interior [16,17,[51][52][53] (see [54], however). Their amplitudes tend to be proportional to β 2 E −α , with α ranging from 0 to 2 [52,55,56], depending on the excitation frequency.…”
Section: -2mentioning
confidence: 99%
“…The saturation of the instability can lead to either sustained flows [15][16][17] or cyclic behaviors between laminar and turbulent states [12,[18][19][20], reminiscent of the "resonant collapse" of inertial waves observed by McEwan [21]. The presence or absence of geostrophic modes appears to be important, but the diversity remains to be explained in detail.…”
mentioning
confidence: 99%
“…Our paper builds upon the recent laboratory experimental work by Grannan et al,22 where quantitative measurements were only available for the horizontal flow in the equatorial plane. We therefore complement their experimental results with high-resolution direct numerical simulations (DNS), from which a complete three-dimensional description of the flow is available.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] as in axisymmetric cases, but also of a topographic nature. Although librational forcing cannot directly excite eigenmodes of the system through a direct resonance in the inviscid case, 18,19 it has been shown that three-dimensional flows can be driven by the resonance of two inertial modes with an elliptically deformed base flow, 4,[20][21][22] the so-called libration-driven elliptical instability (LDEI). More generally, the elliptical instability 23 is a resonance mechanism between a pair of normal modes of the system and the underlying strain field associated with regions of two-dimensional, elliptical streamlines.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests an alternative way to break TPT. The Coriolis force can supply the restoring force that supports so-called inertial oscillations and waves in rotating fluids [79][80][81][82]. These inertial flows allow for an oscillatory-style of rotating columnar-style convection, which is typically more easily excited in low P r fluids than the steady form of convection.…”
Section: Essential Theorymentioning
confidence: 99%